An analytical study to determine the mechanical tolerances for the afterburner superconducting undulators at EuXFEL. Issue 1 (1st December 2022) - Grattoni, V.; Casalbuoni, S.; Marchetti, B.
Abstract: At the European XFEL, a superconducting afterburner is planned for the SASE2 hard X-ray beamline. It will consist of 5 undulator modules plus a pre-series module called S-PRESSO. Within each module, two superconducting undulators (SCU) 2 m long are present. Such an afterburner will enable photon energies above 30 keV. The magnetic field of the SCU determines the quality of the electron beam trajectory and the free-electron laser (FEL) radiation. The mechanical accuracy of the SCU determines its magnetic field quality. In this contribution, we present the mechanical errors and an analytical study to determine the tolerances for our SCUs.